2013
DOI: 10.1186/cc13173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clinically relevant acute hypercapnic and metabolic acidosis on the cardiovascular system: an experimental porcine study

Abstract: IntroductionHypercapnic acidosis (HCA) that accompanies lung-protective ventilation may be considered permissive (a tolerable side effect), or it may be therapeutic by itself. Cardiovascular effects may contribute to, or limit, the potential therapeutic impact of HCA; therefore, a complex physiological study was performed in healthy pigs to evaluate the systemic and organ-specific circulatory effects of HCA, and to compare them with those of metabolic (eucapnic) acidosis (MAC).MethodsIn anesthetized, mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 34 publications
(40 reference statements)
5
50
1
5
Order By: Relevance
“…Although BD is strictly a calculated value, pH is a direct measurement reflecting the collective metabolic effects of oxygen debt, metabolic buffering, and compensatory respiration. Reductions in pH have significant physiologic effects on multiple-organ systems [25,26]. Our data show that physiologic correspondence between pH and BD deteriorated by 24e48 h after injury.…”
Section: Discussionmentioning
confidence: 65%
“…Although BD is strictly a calculated value, pH is a direct measurement reflecting the collective metabolic effects of oxygen debt, metabolic buffering, and compensatory respiration. Reductions in pH have significant physiologic effects on multiple-organ systems [25,26]. Our data show that physiologic correspondence between pH and BD deteriorated by 24e48 h after injury.…”
Section: Discussionmentioning
confidence: 65%
“…This reduction was clearly related to the correction of HCA. HCA enhances pulmonary vasoconstriction . Several clinical studies demonstrated that HCA causes an increase in mean PAP in ARDS .…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians seldom use very low tidal volumes in practice because of the clinical acceptability of this ‘permissive’ hypercapnia. Indeed, despite some potential beneficial anti‐inflammatory effects, it is well established that hypercapnic acidosis (HCA) has deleterious effects, in particular by contributing to increase constriction within the pulmonary vasculature …”
mentioning
confidence: 99%
“…Similarly, hypercapnia also contributes to the elevation of PAP, and it has been proposed that increases in pulmonary vascular resistance (PVR) and cardiac output (CO) additively work as the pathogenesis of PAH (11)(12)(13). In addition, respiratory acidosis due to high CO 2 partial pressure can also cause PAP escalation [9,10].…”
Section: Introductionmentioning
confidence: 99%